Gaps in Software Testing Education: A Survey of Academic Courses in Sweden - Barrett, Ayodele A.; Enoiu, Eduard P.; Afzal, Wasif (IEEE/ACM International Conference on Software Engineering: Software Engineering Education and Training (Online), 2025)
A cross-sectional, questionnaire-based survey of software testing courses offered at Swedish universities was undertaken in the final quarter of 2023. With a return rate of 44%, the survey delved into the contents of these software testing courses to gain an understanding of how the courses differ in terms of depth and breadth of content. Information was also sought about administrative and course planning activities related to the courses. Some key findings are that there is in-depth coverage of unit testing in all the courses, with none of the courses offering in-depth testing of other test levels such as acceptance testing. Also notable is the difference in test types. As an example, functional testing is taught in-depth in all the courses, while accessibility testing is not taught at all in half of the courses. It is suggested that a greater range of software testing topics is needed in future education if more stakeholders, such as business analysts and software developers, not just software testers, are to have a quality-centred approach to software development.